Análise da influência do diâmetro do agregado graúdo nas propriedades do estado fresco e endurecido do concreto estrutural - Reis, Vinicius Quadros (2018)
Concrete, usually made up of coarse aggregates, sand, cement and water, is currently one of the main components used in the construction of structural elements. Thus, qualitative research of the materials that compose it, become essential in the technological improvement of the same. Because it is composed of other materials, called primers or formers, the concrete ends up expressing in its properties, variable characteristics that come from its formation process and the materials used. The aim of this research was to analyze the influence of the variation of the diameter of the coarse aggregates of basaltic on the concrete properties with a structural character. The characteristics of the fresh state were emphasized, such as the conical truncation of the sample, the air content, and also in the hardened state, showing mainly the compressive strength and modulus of elasticity. In a complementary way, the experimental values obtained for the static elastic modulus were compared with the national standard NBR 6118/2014, and the main international standards such as ACI 318, EUROCODE 2/2004 and CEB Model Code/2010. The methodology of dosing and confection of concrete test bodies was according to the Brazilian Association of Portland Cement (ABCP). As for the results obtained, it was evidenced in terms of abatement and plasticity, that concrete with smaller aggregates present greater cohesion between the particles and the cement paste. Regarding the compressive strength, it was evidenced that smaller aggregates, such as gravel 0, result in a significant increase in the value of the property, a fact that is not observed for the modulus of elasticity, which shows an egalitarian behavior for all bands of coarse aggregates used in the preparation of samples. When comparing the experimental and theoretical values of the static modulus of elasticity, there was variation in the estimation performed by each standard, some of them with more conservative characteristics.